Expectations in Experiments - Florian Wagener (Tinbergen Institute, 2013)
The rational expectations hypothesis is one of the cornerstones of current economic theorising. This review discusses a number of experiments that focus on expectation formation by human subjects and analyses the implications for the rational expectations hypothesis. The experiments show that most agents are weakly rational and that their expectations coordinate quickly; but the strong rational expectations hypothesis poorly describes the expectational dynamics and is outperformed by other hypotheses.
Keywords: D84; 330; Rational expectations; expectation formation; laboratory experiments; human subjects